Asfaltitin bitüm ve bitümlü sıcak karışımların mekanik özelliklerine etkisi - Kök, Baha Vural; Yılmaz, Mehmet; Kuloğlu, Necati (My University, 2012)
Bu çalışmada Şırnak (Silopi) bölgesinden temin edilen asfaltit B160/220 bitümüne ağırlıkça %2, %4, %6 ve %8 oranlarında ilave edildi. Orjinal bitüm ve asfaltit katkılı modifiye bitümlerin mekanik özellikleri incelendi. Asfaltit ilavesi ile standart penetrasyonun azaldığı, viskozite ve kompleks modülünün arttığı, yumuşama noktası ve faz açısı değerlerinde ise kayda değer değişimler olmadığı görüldü. Marshall numuneleri üzerinde yapılan test sonuçları bitüme asfaltit katılması ile kalıcı Marshall stabilitesinde, indirekt çekme oranında, 15ºC, 25ºC ve 35ºC sıcaklıklardaki rijitlik modülünde ve yorulma ömründe artışlar olduğunu gösterdi. Sonuç olarak, bitüme belli oranlarda asfaltit katılmasının bitümlü sıcak karışımların neme karşı direncini ve mekanik özelliklerini etkili şekilde iyileştirebileceği görüldü. Test edilen karışımlar için %4 asfaltit katkı oranının optimum olduğu belirlendi.

In this research the asphaltite obtained from Şırnak (Silopi) region was added to B160/220 bitumen by 2%, 4%, 6% and 8% by weight. The mechanical properties of original bitumen and asphaltite added (modified) bitumen were investigated. It was observed that standard penetration was reduced, viscosity and complex modulus were increased and there was no noticeable change on softening point and on phase angle by the addition of asphaltite. The test results on the Marshall specimens showed that retained Marshall stability, indirect tensile strength ratio, stiffness modulus at temperatures of 15?C, 25?C and 35?C and fatigue life were significantly increased by the addition of asphaltite to bitumen. In conclusion, it is seen that the addition of certain amounts of asphaltite to bitumen can effectively improvethe mechanical properties and moisture resistance of hot bituminous mixes. It was determined that 4% asphaltite content is optimum for the mixtures tested.
The effects of addition of asphaltite on the mechanical properties of bitumen and bituminous hot mixes
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Asfaltit; Modifiye bitüm; Modifiye bitümlü sıcak karışım; Mekanik özellikler; Remove selected; Modified bitumen; Modified bituminous hot mix; Mechanical properties; Asphaltite